Reinterpret Panji Roman in bedhaya gandrungmanis lost choreography - Naufal Anggito Yudhistira; I Made Suparta; Mamlahatun Buduroh; Turita Indah Setyani (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Bedhaya Gandrungmanis is one of the Bedhaya dance which was created in the 19th century during Pakubuwana VIII's reign in Keraton Surakarta. This dance narrates Panji Jayakusuma's text, which symbolizes political chaos in 19th century Keraton Surakarta. The dance itself could represent how Panji roman used by Keraton Surakarta to construct the idea of Javanese kingship. This research tries to put forward an understanding of Bedhaya Gandrungmanis, which had been fragmented and lost, based on manuscripts and oral tradition. This research uses an ethno-philological method, which integrates philological research in anthropological perspectives. Data collecting technique includes collecting philological data on manuscript research in Keraton Surakarta Library, Universitas Indonesia Library, and Pura Mangkunegaran Library, and also collecting ethnographic data by interview, field research, and observation. The earliest version of Bedhaya Gandrungmanis was interpreted as a symbol of royal succession. In the last version of the 20th century, Bedhaya Gandrungmanis was re-interpreted in more romantic terms and lost its political resonance. The Panji story in this dance comes from the Panji Jayakusuma story that formed by Pakubuwana VIII to symbolize cultural change in the 19th century during the Dutch Colonial era. Its meaning had been shifted and fragmented as a result of these cultural changes.